Here's the question you clicked on:
mariannu
Solve the linear system using elimination. Hello you guys. I just want to know how you flip it. 2x - y= -11 y = -2x -13
rewrite the second equation by adding 2x to both sides.
for the second equation \[y=-2x-13\] you already solved for y. plug that y into the first equation, giving you\[2x-(-2x-13)=-11\]
So chrismoon, you are instructing the asker to ignore the directions which say to solve using elimination?????
ALl I just want to know is just how to flip it. and thats it.
@mariannu Do what I said and then add the two equations to eliminate y from the system
What do you mean by flip it?
So its y + 2x = -11???
Ok that makes more sense thank you! ^.^ for the help. So I just do that for other equations like that right?
Do you mean other systems?
If so, the answer is yes.
Ok, thank you much!!! ^.^ lol
You're given two things: Equation 1)\[2x-y=-11\]Equation 2) \[y=-2x-13\] Equation 2 tells you what y is already. You can put what y equals (-2x-13 in this case) into the first equation for y. Equation 1 goes from \[2x-y=-11\] to \[2x-(-2x-13)=-11\] since\[y=-2x-13\] Simplify your Equation 1 from \[2x-(-2x-13)=-11\] to \[2x+2x+13=-11\]giving you \[4x=-24\] divide both sides by 4 to solve for x \[x=-6\] Now that you have solved for x, go all the way back to the original Equation 2\[y=-2x-13\] Since we know what x is now, plug it in\[y=-2(-6)-13\]giving us \[y=-1\] There you have it: \[y=-1\]and \[x=-6\]
@chrismoon Why do you keep telling the asker to ignore the directions given?
Sorry, didn't see you guys already talked about it before I posted. Didn't get notified you guys got it taken care of.
@chrismoon The problem says to solve by elimination. You keep telling the asker to use substitution.
Guess I didn't read the question very thoroughly. My bad.
That is ok. As you try to help. but thanks